PENGARUH LATIHAN SNAKE JUMP AGILITY LADDER DRILLTERHADAP KELINCAHAN PADA SSBU-15 PTPN V - Purwandi, Wira; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem in the research that the agilityPTPN V SSB U-15 is still lacking, this from the various test and tournament and tesis one of the causes of the defeat.This type of research is a kind of research experiments to see the effects of this form of exercise that is given. The purpose of this research was to observe the effect of practice snake jump "agility ladder drill " of agility on SSB U-15 PTPN V Pekanbaru with respondents 16 people. Sampling Technique using total sampling, where the total population is sampled. Data Collection techniques derived from the pre-test and post test. Instrument in this research using illinois agility run test to see agility. Analyses were performed using t-test. Based on data analysis and discussion it can be concluded that there is significant effect from a exercises snake jump “agility ladderdrill”to agility in SSB U-15 PTPN V as evidance by Ttest4,66 and T Table 1.75. It means T test > T table at the level of α = 0.05.Keyword : snake jump “agility ladder drill”, agility, football.